The Role of the Principal in Improving Teacher Performance at Al-Falah Nagreg Private Vocational High School (SMKS) Kab. Bandung - Ujang Cepi Barlian; Syahruna Mubarokah; Yuni Rahmawati; Dwi Rahayuningsih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research is descriptive in nature, only limited to an attempt to reveal a problem, situation or event as it relates to the research problem in improving teacher performance at SMKS Al-Falah Nagreg. Based on the results of observations and interviews, the authors see that the principal of SMKS Al-Falah Nagreg, Mr. Ahmad Akbar, S.S., M.Pd, has performed his role quite well. The leadership role of the principal in improving teacher performance at Al-Falah Nagreg Vocational High School is related to the teacher's performance carried out by the teacher in teaching in class so that the teacher must be given direction and guidance. The principal has carried out his leadership role in improving teacher performance well. In carrying out his role the school principal has adopted a democratic and open leadership style, and emphasized teachers to be disciplined, guided teachers and helped teachers to solve problems faced by teachers, directed teachers and provided training to teachers to improve their abilities, and conducted class visits. In planning, the school principal creates programs that support improving teacher performance in schools such as holding annual In House Training/Workshops, improving learning facilities, planning teacher training and apprenticeships, and making disciplinary programs and class visits. Schools always carry out In House Training, teacher training and apprenticeships every year, with the target that teachers can produce learning that is in line with the business world and the industrial world. In practice, the school principal always holds In House Training/Workshops for all teachers, one of the targets of which is to make a Learning Plan for use in the New Academic Year. The school principal has carried out class visits at the beginning of the semester, and has increased the need for learning facilities in schools. Several educators have carried out training and internships in several companies. Evaluation of teacher performance is used to measure the achievement of teacher criteria set by the school. This evaluation is carried out at the end of each semester as material to improve teacher performance in the following semester. This action is said to be successful with measurable improvements in teacher performance every semester